Environmental ethics in KS Maniam’s Between Lives and Yang-May Ooi’s The Flame Tree - Zainal, Zainor Izat (SAGE Publications, 2017)
Criticism on Malaysian literature in English rarely addresses environmental concerns and in this article I attempt to redress this by examining two contemporary Malaysian novels in English, KS Maniam’s (2003) Between Lives and Yang-May Ooi’s (1998) The Flame Tree. This article investigates some of the environmental ethics suggested by these Malaysian writers, based on four important arguments for “doing” environmental ethics: duty, character, relationships and rights. Analyses of the novels reveal an environmental ethics that seems to revolve around the profound ideas that we are part of the environment, that the future of the environment hinges on actions and knowledge to ensure its sustainability and that action is derived from a sense of shared duty and activism and having good character and relationships. Also revealed in these texts is the commendable influence of religious beliefs and traditions and how these are interwoven with current ethical concerns about the environment and its sustainability.